Respon Ekspresi Molekul Adhesi pada Kultur Sel Endotel yang diinduksi LDL Teroksidasi dari Macaca fascicularis terhadap Ekstrak Kurkuminoid Temumangga - Trini Susmiati; Sulistiyani .; Dondin Sajuthi; Latifah K. Darusman (Pusat Studi Satwa Primata LPPM-IPB, 2009)
Curcuminoids of Curcuma manggo believed to have antioxidant properties that can prevent the occurrence of atherosclerosis. However, the mechanism at the molecular level is not clearly known. Increase in intracellular adhesion molecule-1 (ICAM-1) will result in endothelial cell dysfunction that initiates athersclerosis. The expression of ICAM-1 can be triggered by oxidized LDL molecules. The purpose of this study is to elucidate the effects of curcuminoids temumangga (Curcuma mango) on the expression of ICAM-1 induction in endothelial cell culture. Prior to the induction of the expression of ICAM-1, endothelial cell culture was pre-incubated with curcuminoids extract for 48 hours with concentration of 2 ppm and 8 ppm, then further incubated with oxidized LDL for 24 hours. The treated cells were compared to 5 µM Cu2+ induced endothelial cell culture with or without LDL from Macaca fascicularis. ICAM-1 expression was determined by immunohistochemistry using anti-ICAM-1 antibodies and visualized with staining by 3.3-diaminobenzidin tetrahidrochloride (DAB). Results showed that surface-induced endothelial cell culture with ion Cu2+ stained well by DAB as brown yellow, which indicates ICAM-1 expression. Curcuminoids extract of 8 ppm reduced induction of ICAM-1 response. Induction of ICAM-1 expression by oxidized LDL caused foam cell accumulation in addition to ICAM-1 expression.Key words: Curcuminoid, low density lipoprotein (LDL), Macaca fascicularis, intracellular adhesion molecule-1 (ICAM-1), immunohistochemistry